Prostitution - Daniel-Hughes, Carly (The Oxford handbook of New Testament, gender, and sexuality, 2019)
This chapter shows how slavery informed the social realities of and rhetoric about prostitution and prostitutes, which informed the negative representation of female prostitutes in early Christian sources. Following Paul’s rhetoric, many Christians used sexual virtue to legitimatize themselves and bolster their triumphalist claims over others in the Roman Empire. To this end, they employed the degraded and debased female prostitute as a powerful symbolic figure as that which stood outside communal boundaries or as a threat that could undermine boundaries from within. In so doing, they marginalized prostitutes and enslaved persons, who could not, by virtue of their enslavement, sustain the sexual ethics that early Christians were promoting. The chapter concludes with debates about contemporary sex workers, arguing that it is critical for feminist historians to resist the rhetoric of the early Christian texts, which obscure the presence of prostitutes (and vulnerable slaves) in ancient Christ-believing communities.